Emergence of mobile tigecycline resistance mechanism in Escherichia coli strains from migratory birds in China. Issue 1 (1st January 2019) - Chen, Chong; Cui, Chao-Yue; Zhang, Yan; He, Qian; Wu, Xiao-Ting; Li, Gong; Liao, Xiao-Ping; Kreiswirth, Barry N.; Liu, Ya-Hong; Chen, Liang; Sun, Jian
ABSTRACT: Plasmid-mediated antimicrobial resistance has emerged as one of the principal global issues, posing significant threats to public health. Herein, we reported a mobile tigecycline resistance mechanism Tet(X4) on both plasmid and chromosome in Escherichia coli strains from migratory birds in China. Besides tigecycline, these tet (X4)-positive strains also exhibited elevated MICs to the FDA newly approved tetracycline antibiotics, eravacycline (4 µg/ml) and omadacycline (8 µg/ml). Worrisomely, the tet (X4)-carrying plasmids and chromosome also shared high homology with the plasmids from human. Taken together, Tet(X4) represents another emerging antimicrobial threat and collective efforts from different sectors are needed to control its further spread.